Penerapan Mumāṡalah dalam Hukuman Kisas (Studi Komparasi Mazhab Syafii dan Hambali) - Muh Syahrul; Rapung Rapung; Irsyad Rafi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to find out how the concept of mumasalah in Islamic jurisprudence, as well as to find out more about the differences in opinions of the Shafii and Hambali schools regarding mumasalah in the punishment of kisas. The type of research used is qualitative descriptive research using library research methods and supported by comparative approach methods. From the results of this research, it was found that mumasalah in Islamic jurisprudence is a matter recognized by the Shari'a, it can even be said to be the original law of practical Islamic laws, especially the laws required of equality. The Shafii School prefers to apply mumasalah in the punishment of kisas, because they see it as more about justice for the victim's guardian, and more to ease their anger over the treatment or way the perpetrator killed the victim. The Hambali school is more inclined to apply kisas using swords